1998
DOI: 10.1016/s0738-3991(98)00065-2
|View full text |Cite
|
Sign up to set email alerts
|

Using pictographs to enhance recall of spoken medical instructions

Abstract: Pictographs have been used in nonliterate societies to help people remember spoken instructions and, today, they could be used to help nonliterate people remember spoken medical instructions. This study tested the hypothesis that pictographs can improve recall of spoken medical instructions. Twenty-one junior college subjects listened to lists of 38 actions for managing fever and 50 actions for managing sore mouth. One of the action lists was accompanied by pictographs during both listening and recall while th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
156
0
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(165 citation statements)
references
References 4 publications
5
156
0
4
Order By: Relevance
“…The infographics retrieved for this study often contained concussion-related information which had been presented in a format suitable for the image-sharing site, and as such they could constitute a means of promoting concussion awareness and education. This finding is encouraging in light of previous work indicating that real-life images are effective in conveying health information (Houts et al, 1998(Houts et al, , 2006 and also that infographics are popular visual communication tools for relaying complex health information (Smiciklas, 2012). In a recent content analysis of Chronic Obstructive Pulmonary Disease-related Pinterest images, the authors found that images of real people and infographics depicting self-management information received the greatest amount of user engagement though user comments and "likes" (Paige et al, 2015).…”
Section: Information Qualitysupporting
confidence: 74%
See 1 more Smart Citation
“…The infographics retrieved for this study often contained concussion-related information which had been presented in a format suitable for the image-sharing site, and as such they could constitute a means of promoting concussion awareness and education. This finding is encouraging in light of previous work indicating that real-life images are effective in conveying health information (Houts et al, 1998(Houts et al, , 2006 and also that infographics are popular visual communication tools for relaying complex health information (Smiciklas, 2012). In a recent content analysis of Chronic Obstructive Pulmonary Disease-related Pinterest images, the authors found that images of real people and infographics depicting self-management information received the greatest amount of user engagement though user comments and "likes" (Paige et al, 2015).…”
Section: Information Qualitysupporting
confidence: 74%
“…Therefore, in Ref(s). Ahmed et al, 2010;Ahmed et al, 2012;Houts et al, 1998;Houts et al, 2006;McCrory et al, 2012;McCrory et al, 2008;Moorhead et al, 2013;Paige et al, 2015;Provvidenza et al, 2013;Sullivan et al, 2012;Williams et al, 2014;Yom Tov et al, 2012; please list all names for up to 6 authors/ editors. For more than 6 authors/editors, use 'et al' after the first 6 authors/editors.…”
Section: Q3mentioning
confidence: 99%
“…10 Evidence supports that delivery of patient information is most efficient and meaningful when it is presented in small quantities to decrease cognitive load, well timed in response to a patient's readiness to learn, and rich with the use of multimedia images. [14][15][16] Objective Despite the documented need for information among patients and families, ICU educational content is often not centrally located or organized to make it easily accessible to patients and families within an ICU. To facilitate such communication, it is important to identify a core set of information that is generally applicable to all ICU patients and families.…”
mentioning
confidence: 99%
“…There was statistically significant difference when levels of educa- The study 25 found that there was no bivariant relation between literacy and adherence (p=0.88), whereas Kalichman et al mentioned that lower literacy was associated with greater odds of poor adherence. [26][27] Similarly, patients with better compliance have better knowledge about the drugs and lifestyle modifica- …”
mentioning
confidence: 99%